2005
DOI: 10.1002/j.0022-0337.2005.69.3.tb03927.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Information and Communication Technology Among Dental Students at the University of Jordan

Abstract: The aim of this study was to investigate the current knowledge, skills, and opinions of undergraduate dental students at the University of Jordan with respect to information communication technology (ICT). Dental students from the second, third, fourth, and fifth years were asked to complete a questionnaire presented in a lecture at the end of the second semester in the 2002-03 academic year. The response rate was 81 percent. Besides free and unlimited access to computers at the school of dentistry, 74 percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

18
50
2
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(72 citation statements)
references
References 22 publications
18
50
2
1
Order By: Relevance
“…Indian female dental students are performing as good as their US counterpart with respect to be equal to males in the computer use. Similarly more male dental undergraduate students from Jordan felt competent with basic IT skills but no such difference was noticed among the present study showing females equally competent (2). A similar study among Greek post graduate students also showed higher computer literacy scores among males (11).…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…Indian female dental students are performing as good as their US counterpart with respect to be equal to males in the computer use. Similarly more male dental undergraduate students from Jordan felt competent with basic IT skills but no such difference was noticed among the present study showing females equally competent (2). A similar study among Greek post graduate students also showed higher computer literacy scores among males (11).…”
Section: Discussioncontrasting
confidence: 56%
“…Japan offers a total of 788 hours for general educational courses which includes training in computer science (20). In Jordan all schools provide mandatory basic computer training to the students and all teaching staff is required to obtain a Jordan University Computer Driving License (2). Even short term training programs have shown to increase the knowledge of computers among students (9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Manuscript to be reviewed students with respect to information communication technologies, the skills of male students were found to be better than those of female students, and that they were more familiar in the use of computers, and also longer users of computers (Rajab & Baqain, 2005). Despite the study of Brumini et al (2014) and a similar study of Rajab and Baqain (2005), the m-learning attitude scale's total score for males in the current study were found to be statistically significant and higher than that of the females. Moreover, students with portable power supply units were found to reveal statistically higher m-learning attitude scale total scores than those who did not carry such units.…”
Section: Discussionmentioning
confidence: 99%